2012
DOI: 10.1063/1.4764917
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed terahertz radiation due to coherent phonon-polariton excitation in 〈110〉 ZnTe crystal

Abstract: Pulsed terahertz (THz) radiation, generated through optical rectification (OR) by exciting [110] ZnTe crystal with ultrafast optical pulses, typically consists of only a few cycles of electromagnetic field oscillations with a duration about a couple of picoseconds. However, it is possible, under appropriate conditions, to generate a long damped oscillation tail (LDOT) following the main cycles. The LDOT can last tens of picoseconds and its Fourier transform shows a higher and narrower frequency peak than that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…A typical Fourier transform of the LDOT as shown in Figure 6B clearly reveals two peaks at 2.6 and 3.7 THz. The 2.6 THz peak is associated with the formation of phonon polariton due to the hybridization of pump‐induced THz radiation and the TO phonon in ZnTe 4,6,8 . We found that the phonon and phonon polariton amplitude both increase linearly with pump power up to 60 mW (corresponding to 120 μJ/cm 2 ), as is shown in Figure 6C.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…A typical Fourier transform of the LDOT as shown in Figure 6B clearly reveals two peaks at 2.6 and 3.7 THz. The 2.6 THz peak is associated with the formation of phonon polariton due to the hybridization of pump‐induced THz radiation and the TO phonon in ZnTe 4,6,8 . We found that the phonon and phonon polariton amplitude both increase linearly with pump power up to 60 mW (corresponding to 120 μJ/cm 2 ), as is shown in Figure 6C.…”
Section: Resultsmentioning
confidence: 51%
“…Fourier transform of the LDOT shows the central frequency to be at 2.36 THz, which is noticeably lower than previously determined using OPOP (Figures 6 and 7). In a previous report using OPTE, the phonon polariton frequency is found to be between 1.9 and 2.7 THz, depending on the central frequency and the pulse duration of the pump beam 6 . More specifically, 1.9 THz (2.7 THz) corresponds to 800 nm (750 nm) pump.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Few-cycle terahertz (THz) electromagnetic pulses have attracted much attention because they have high potential in fundamental studies and practical applications [1]. Inorganic crystals, such as ZnTe, GaSe:Te, used as THz emitters equipped with ultrafast lasers have become popular and high signal-to-noise ratio tabletop THz sources around the world [2][3][4][5]. Recently, intense THz pulses have been demonstrated in LiNbO 3 by using tilted pulse front excitation, which has extended the applications of THz radiation into the nonlinear region [6,7].…”
Section: Introductionmentioning
confidence: 99%